Specific NLRP3 Inflammasome Assembling and Regulation in Neutrophils: Relevance in Inflammatory and Infectious Diseases - Christophe Paget; Emilie Doz-Deblauwe; Nathalie Winter; Benoit Briard (Cells, 2022)
The NLRP3 inflammasome is a cytosolic multimeric protein platform that leads to the activation of the protease zymogen, caspase-1 (CASP1). Inflammasome activation mediates the proteolytic activation of pro-inflammatory cytokines (IL-1β and IL-18) and program cell death called pyroptosis. The pyroptosis is mediated by the protein executioner Gasdermin D (GSDMD), which forms pores at the plasma membrane to facilitate IL-1β/IL-18 secretion and causes pyroptosis. The NLRP3 inflammasome is activated in response to a large number of pathogenic and sterile insults. However, an uncontrolled inflammasome activation may drive inflammation-associated diseases. Initially, inflammasome-competent cells were believed to be limited to macrophages, dendritic cells (DC), and monocytes. However, emerging evidence indicates that neutrophils can assemble inflammasomes in response to various stimuli with functional relevance. Interestingly, the regulation of inflammasome in neutrophils appears to be unconventional. This review provides a broad overview of the role and regulation of inflammasomes—and more specifically NLRP3—in neutrophils.